Production and Perception of Classroom Disturbances - Boris Eckstein (EARLI, 2019)
Classroom disturbances impair the quality of teaching and learning, and they can be a source of strain for both teachers and students. Some studies indicate, however, that not everyone involved gets equally disturbed by the same occurrences. Altogether, there is still little solid knowledge about the teachers' and the students' subjective perception of disturbance. Moreover, rater effects may have confounded the findings available. Addressing these desiderata, the SUGUS study investigates two elements of classroom disturbances within an interactionist framework: the incidence of deviant behaviour shown by particular target students, and the intensity of disturbance as subjectively perceived by teachers, by classmates, and by the targets themselves. For this purpose, we conducted a questionnaire survey among 85 primary-school class teachers and 1412 students. The data were analysed by means of a two-level correlated trait - correlated method minus one [CT-C(M-1)] model. This relatively novel statistical procedure has only rarely been applied in educational research so far. It made it possible to determine the respondents'common view on classroom disturbances as well as the rater-specific perspectives. The results indicate that increasing deviance coincides with increasing distraction and annoyance - but mainly in a relatively small intersection of the different perspectives. Beyond that, the analysis revealed substantial rater effects which explain 30 to 61% of variance in teacher ratings, for instance. The author discusses likely reasons why disturbances are perceived so divergently.